A mixed methods evaluation of team-based learning for applied pathophysiology in undergraduate nursing education. (February 2018) - Branney, Jonathan; Priego-Hernández, Jacqueline
Abstract: Background: It is important for nurses to have a thorough understanding of the biosciences such as pathophysiology that underpin nursing care. These courses include content that can be difficult to learn. Team-based learning is emerging as a strategy for enhancing learning in nurse education due to the promotion of individual learning as well as learning in teams. Objectives: In this study we sought to evaluate the use of team-based learning in the teaching of applied pathophysiology to undergraduate student nurses. Design: A mixed methods observational study. Methods: In a year two, undergraduate nursing applied pathophysiology module circulatory shock was taught using Team-based Learning while all remaining topics were taught using traditional lectures. After the Team-based Learning intervention the students were invited to complete the Team-based Learning Student Assessment Instrument, which measures accountability, preference and satisfaction with Team-based Learning. Students were also invited to focus group discussions to gain a more thorough understanding of their experience with Team-based Learning. Exam scores for answers to questions based on Team-based Learning-taught material were compared with those from lecture-taught material. Results: Of the 197 students enrolled on the module, 167 (85% response rate) returned the instrument, the results from which indicated a favourable experience with Team-based Learning. Most students reported higher accountability (93%) and satisfaction (92%) with Team-based Learning. Lectures that promoted active learning were viewed as an important feature of the university experience which may explain the 76% exhibiting a preference for Team-based Learning. Most students wanted to make a meaningful contribution so as not to let down their team and they saw a clear relevance between the Team-based Learning activities and their own experiences of teamwork in clinical practice. Exam scores on the question related to Team-based Learning-taught material were comparable to those related to lecture-taught material. Conclusions: Most students had a preference for, and reported higher accountability and satisfaction with Team-based Learning. Through contextualisation and teamwork, Team-based Learning appears to be a strategy that confers strong pedagogical benefits for teaching applied pathophysiology (bioscience) to student nurses. Highlights: Team-based learning (TBL) promotes individual and group learning in nurse education. TBL elicits higher accountability and satisfaction than standard teaching methods such as lectures. TBL is preferred vis-à-vis lectures, but lectures remain a valued university expectation. TBL activities promote grasping the importance of teamwork in nursing clinical practice. TBL confers strong pedagogical benefits to student nurses' learning the bioscience underpinning nursing care.